(untitled) (Journal of Behavioral Public Administration, 2022)
Editor’s note. In this roundtable, the contributors discuss the role of institutions (or lack thereof) in behavioral public administration (BPA). In a multidisciplinary discourse, the contributors touch on the many tensions that exist between institutional and behavioral perspectives of public administration. This roundtable is intended to spark additional discourse on the role of institutions in how they parameterize behaviors within or how individual behaviors might, in the aggregate, influence the norms and rules that shape institutions. Here at JBPA, we encourage further dialogue on the role of institutions in behavioral studies and holding work from a macro-, meso-, and micro-lens accountable to each another (Jilke et al., 2019). The editorial team at JBPA is thankful to Herbert Simon Award (Midwest Political Science Association) winners Anthony Bertelli (2020) and Norma Riccucci (2021) for organizing this thoughtful conversation. We hope that the discussion offered in this roundtable will inspire further inquiry from our readers. We encourage thought leaders in the field of public administration and beyond to continue this conversation here at JBPA. Therefore, we are announcing a Call for Papers, in response to this roundtable. Contributing papers can take one of several forms: (1) Research Letters (of no more than 2,000 words), for instance, might provide replications of existing work in BPA where the replications newly account for institutional embeddedness. (2) Perspective and Practices submissions (generally limited to 4,000 words) should be written as thoughtful responses to the discourse below, and (3) Research Articles (up to 8,000 words) can be more thoroughly threshed out theoretical conceits about institutions in BPA. • William G. Resh, Editor-in-Chief